PHYSICAL AND CHEMICAL EXPERIMENTS IN HIGH-SOCIETY SALOONS OF THE LAST DECADE OF 18TH — FIRST QUARTER OF 19TH CENTURY - Lupanova Ye.M. (Вестник Брянского государственного университета, 2022)
Physical and chemical experiments attract attention as bright and unusual shows. Pedagogues and museum specialists explore them as a motivating element to awake interest to study the subject. History of enlightening shows roots to the first years of St. Petersburg Academy of Sciences and the Kunstkamera functioning. Gradually growing fashion came to its peak to the last decade of the 18th century and got its visualization as a series of popular books addressed to wide circle of readers. These editions revealed the secrets of different entertainments based on the modern knowledge of scientific laws. Until now literature of this kind was not used as a historical source. It provides the opportunity to have a new view on the processes of enlightenment and education in Russian society. The earlier books are characterized as the closeset to the idea of science popularization, later − as tending to pure entertainment, the ones in the middle − as the richest with the information of practical significance. The development of the genre went the way of social-request satisfaction, that meant entertainment with the least possible dull explanations. The analogue with modern processes of popular educational projects development is quite obvious, but modern state of wide-society interests is even advantageous for realizing the ideas of enlightenment.